Knowledge, attitude, and diabetes self-care among individuals at high-risk of diabetes-related blindness in Bangladesh: a cross-sectional study - Shahina Pardhan; Md. Saiful Islam; Raju Sapkota (BMC Public Health)
Abstract Background/Aim Adequate knowledge, attitude, and self-care practice (KAP) are paramount in reducing diabetes complications. This study examined diabetes-related KAP in individuals who have been previously reported to be at a higher risk of blindness such as those on insulin treatment or with a longer (>6 years) duration of diabetes in Bangladesh. Methods Six hundred community-dwelling individuals (mean age = 52.7±11.6 years) who had been diagnosed with diabetes by their doctor were interviewed. A semi-structured questionnaire obtained self-reported information about diabetes-related KAP, duration, treatment of diabetes, and sociodemographic parameters including age, gender, and education level. Data were collected using a purposive sample technique and analyzed using Fischer’s exact test or independent samples t-tests. Results There were 271 males (45.2%) and 329 (54.8%) females. Of the total participants (mean diabetes duration = 6.6±6.2 years), 36.5% had diabetes for more than the median duration of 6 years, 80.7% were receiving insulin or insulin combined with tablets (insulin group) and the remaining 19.3% were on tablet only and/or diet control (non-insulin group). One-fifth (19.8%) of all the participants did not consider diabetes a serious disease, 31.3% were unaware that uncontrolled diabetes can cause blindness, 40.5% had never had their eyes tested for diabetic retinopathy and 41.5% stated that they would not attend diabetic retinopathy screening until their eyesight became worse. Among those in the insulin group, 42.1% reported being unaware that smoking may be harmful to diabetes compared to 30.2% of those in the non-insulin group (p= 0.02). Additionally, 64.7% of those in the insulin group were unaware that a diabetic retinal screening is different from a routine eye test for spectacles, compared to 44.8% in the non-insulin group (p< 0.001). Sixty-two percent of participants with diabetes duration of more than 6 years reported that diabetes management was a shared responsibility between the doctor and the patient compared to 48.3% with a shorter duration (p< 0.001). Those with a longer duration of diabetes (>6 years) also reported forgetting to take their medication more often than those with a shorter duration (p = 0.02). Twenty-one percent of participants with a duration of diabetes longer than six years had checked their eyes within the previous year compared to 63.5% of those with a shorter duration of diabetes (p< 0.001). Conclusion Individuals on insulin treatment demonstrated poorer knowledge and awareness of diabetes and diabetes eye screening. Those with a longer diabetes duration exhibited poorer self-care practices, particularly not taking the medication regularly, and neglecting diabetic retinal checkups. These issues need to be addressed in designing targeted educational interventions to prevent blindness from uncontrolled diabetes in the high-risk groups in Bangladesh.